Ecdysone response gene E78 controls ovarian germline stem cell niche formation and follicle survival in Drosophila - Ables, Elizabeth T. (Dev Biol, 2015)
Nuclear hormone receptors have emerged as important regulators of mammalian and Drosophila adult physiology, affecting such seemingly diverse processes as adipogenesis, carbohydrate metabolism, circadian rhythm, stem cell function, and gamete production. Although nuclear hormone receptors Ecdysone Receptor (EcR) and Ultraspiracle (Usp) have multiple known roles in Drosophila development and regulate key processes during oogenesis, the adult function of the majority of nuclear hormone receptors remains largely undescribed. Ecdysone-induced protein 78C (E78), a nuclear hormone receptor closely related to Drosophila E75 and to mammalian Rev-Erb and Peroxisome Proliferator Activated Receptors, was originally identified as an early ecdysone target; however, it has remained unclear whether E78 significantly contributes to adult physiology or reproductive function. To further explore the biological function of E78 in oogenesis, we used available E78 reporters and created a new E78 loss-of-function allele. We found that E78 is expressed throughout the germline during oogenesis, and is important for proper egg production and for the maternal control of early embryogenesis. We showed that E78 is required during development to establish the somatic germline stem cell (GSC) niche, and that E78 function in the germline promotes the survival of developing follicles. Consistent with its initial discovery as an ecdysone-induced target, we also found significant genetic interactions between E78 and components of the ecdysone signaling pathway. Taken together with the previously described roles of EcR, Usp, and E75, our results suggest that nuclear hormone receptors are critical for the broad transcriptional control of a wide variety of cellular processes during oogenesis.